2024
DOI: 10.1038/s41590-024-01755-7
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 stabilizes an effector Treg cell program in the tumor microenvironment

Tobias Wertheimer,
Pascale Zwicky,
Lukas Rindlisbacher
et al.

Abstract: Interleukin-23 (IL-23) is a proinflammatory cytokine mainly produced by myeloid cells that promotes tumor growth in various preclinical cancer models and correlates with adverse outcomes. However, as to how IL-23 fuels tumor growth is unclear. Here, we found tumor-associated macrophages to be the main source of IL-23 in mouse and human tumor microenvironments. Among IL-23-sensing cells, we identified a subset of tumor-infiltrating regulatory T (Treg) cells that display a highly suppressive phenotype across mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
(119 reference statements)
0
0
0
Order By: Relevance
“… 39 In a recent research, Tobias Wertheimer et al found tumor-associated macrophages to be the main source of IL-23 in mouse and human tumor microenvironments. 40 Consistent with previous studies, in this work, we found that IL-23, as a severe-irAEs-associated gene, was mainly transcribed by monocytes in human peripheral blood based on scRNA-seq analysis.…”
Section: Discussionsupporting
confidence: 92%
“… 39 In a recent research, Tobias Wertheimer et al found tumor-associated macrophages to be the main source of IL-23 in mouse and human tumor microenvironments. 40 Consistent with previous studies, in this work, we found that IL-23, as a severe-irAEs-associated gene, was mainly transcribed by monocytes in human peripheral blood based on scRNA-seq analysis.…”
Section: Discussionsupporting
confidence: 92%